FACTORS INFLUENCING CONSUMER DECISIONS IN PURCHASING IMPORTED ORANGES AND LOCAL ORANGES (Case Study in Kisaran City) - Mhd Riza Fahlevi; Tumpal HS Siregar; Yohny Anwar (RADJA PUBLIKA, 2024)
This research aims to determine the factors that influence consumer decisions in purchasing imported orange fruit and local orange fruit (case study in Kisaran City). The population in this study was the entire population of Kisaran City, totaling 143,235 people. Determining the sample using interpretive estimation with Structural Equation Modeling (SEM), a purposive sampling approach obtained a total of 150 respondents. Data processing was carried out using the SPSS Statistics 25 program tool. The data analysis technique used was descriptive statistics. validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination. The research results show that cultural factors, personal factors, psychological factors have a positive and significant effect on consumer decisions in purchasing imported citrus fruit, while social factors and price factors have no effect. Then cultural factors, social factors, psychological factors and price factors have a positive and significant influence on consumer decisions in purchasing local citrus fruit, while personal factors have no influence.